2011
DOI: 10.1158/1078-0432.ccr-10-2185
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Profiles Specific to Patient Ethnicity in Lung Adenocarcinoma

Abstract: Purpose: East-Asian (EA) patients with non-small-cell lung cancer (NSCLC) are associated with a high proportion of nonsmoking women, epidermal growth factor receptor (EGFR)-activating somatic mutations, and clinical responses to tyrosine kinase inhibitors. We sought to identify novel molecular differences between NSCLCs from EA and Western European (WE) patients.Experimental Design: A total of 226 lung adenocarcinoma samples from EA (n ¼ 90) and WE (n ¼ 136) patients were analyzed for copy number aberrations (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
71
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 33 publications
10
71
1
Order By: Relevance
“…We previously reported that the frequencies of the aberrant methylation of CpG islands in certain tumor-suppressor genes, such as MGMT and GSTP1, were different between non-Asian populations (American and Australian cases) and Asian populations (Japanese and Taiwanese cases) (23). A recent study that evaluated CNGs in lung adenocarcinomas using a common high-resolution single nucleotide polymorphism microarray, also reported that discrete differences in copy number aberrations was present between East-Asian and Western European individuals (chromosome 16p CNGs in East-Asian individuals, and chromosome 19p losses in Western European individuals) (24). Oncogenes can be activated by mutations, CNGs and/or translocations (11).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the frequencies of the aberrant methylation of CpG islands in certain tumor-suppressor genes, such as MGMT and GSTP1, were different between non-Asian populations (American and Australian cases) and Asian populations (Japanese and Taiwanese cases) (23). A recent study that evaluated CNGs in lung adenocarcinomas using a common high-resolution single nucleotide polymorphism microarray, also reported that discrete differences in copy number aberrations was present between East-Asian and Western European individuals (chromosome 16p CNGs in East-Asian individuals, and chromosome 19p losses in Western European individuals) (24). Oncogenes can be activated by mutations, CNGs and/or translocations (11).…”
Section: Discussionmentioning
confidence: 99%
“…The highest frequency of MET mutations was also found in East Asians. 14,15 In light of these observations, we hypothesized that a Chinese population might present different mutations of the c-kit oncogene in terms of incidence, mutational sites or functional consequence. In our present work, we expanded the mutational analysis of the c-kit oncogene to exons 9, 11, 13, and 17 in Chinese patients with SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, all KRAS mutations were thought to be associated with smoking, however a recent study failed to uphold this relationship, instead a specific type of KRAS mutation was identified that may be influenced by patient smoking status [96,97]. KRAS mutations are more common in western Europeans than in African Americans and Asians [98,99].…”
Section: Krasmentioning
confidence: 99%